Controlling the optical properties of lemongrass extract synthesized gold nanotriangles and potential application in infrared-absorbing optical coatings - Shankar, S. S.; Rai, A.; Ahmad, Absar; Sastry, M. (Chemistry of Materials, 2005)
Anisotropic metal nanoparticles have distinct optical behavior when compared with their spherical counterparts. In this report, we demonstrate a simple method involving the reduction of aqueous gold ions by the extract of the lemongrass plant leading to the formation of gold nanotriangles with interesting absorption in the near-infrared (NIR) region of the electromagnetic spectrum. We show that, by simple variation of the experimental conditions, it is possible to vary the size of the gold nanotriangles and, thus, to tune the absorbance of flat gold nanoparticles in the NIR region. The NIR absorption of the gold nanotriangles is expected to be of application in hyperthermia of cancer cells and in IR-absorbing optical coatings. We show that the lemongrass extract synthesized gold nanotriangles can be easily cast in the form of films on glass substrates and that these films are highly efficient in absorbing IR radiation for potential architectural applications.

Synthesis of gold nanospheres and nanotriangles by the Turkevich approach - Shankar, S. S.; Bhargava, S.; Sastry, Murali (Journal of Nanoscience and Nanotechnology, 2005)
Gold nanoparticles of triangular morphology possess interesting optical properties with potential application in medicine and infrared absorbing coatings, however, little is known about conditions that favor their growth. In this paper, we have reinvestigated a time-tested recipe for the formation of gold nanospheres by citrate reduction of aqueous gold ions under boiling conditions (Turkevich recipe). Our principle findings are that gold nanotriangle formation is kinetically controlled and is highly favored at low temperatures. Furthermore, the presence of chloride ions from the precursor chloroaurate ions plays a major role in promoting the growth of [111] oriented triangular/truncated triangular particles. The presence of bromide and iodide ions that possess the ability to replace surface-bound chloride ions inhibits triangle formation to varying degrees.
Keywords: Crystal growth; Gold; halides; nanospheres; nanotriangles; Temperature effect